Efficacy and Safety of a Novel Botulinum Toxin A for Masseter Reduction: A Randomized, Double-Blind, Placebo-Controlled, Optimal Dose-Finding Study. Issue 1 (January 2021) - Hong, Ji Yeon; Jeong, Guk Jin; Kwon, Tae-Rin; Kim, Jong Hwan; Li, Kapsok; Kim, Beom Joon
Abstract : BACKGROUND: A wide lower face and a square jaw are considered esthetic problems, particularly in Asia. OBJECTIVE: To investigate the optimal dose of a novel botulinum toxin (prabotulinum toxin A) for treating masseteric hypertrophy. METHODS: Ninety subjects with masseteric hypertrophy were randomly divided into 5 groups and treated with placebo (A, normal saline) or prabotulinum toxin A (B: 24, C: 48, D: 72, and E: 96 units). Photography, ultrasonography, and 3-dimensional imaging were performed before and after injection at baseline and at 4, 8, 12, and 16 weeks after treatment. The participants also rated their satisfaction. RESULTS: Masseter thickness significantly reduced in all groups at 12 weeks, compared with that in the placebo group. A dose-dependent reduction in masseter thickness was observed at the resting and maximal clenching positions. Sonography and 3-dimensional imaging revealed a gradual reduction in masseter thickness and volume, respectively, during the first 12 weeks. Despite being slightly effective, a dose of 24 units might be insufficient for resolving square face problems. Patients in Group E reported discomfort during jaw movement. CONCLUSION: Prabotulinum toxin A could effectively improve lower face contour without major complications, with an optimal dose of 48 to 72 units, followed by reinjection after 12 weeks.